Effects of Scaling Up Family Planning on Maternal Survival in Ethiopia: Spectrum Modeling - Kasahun AW; Abebe Adane H; Girum T; Wako WG (Dove Medical Press, 2021)
Abebaw Wasie Kasahun,1 Haimanot Abebe Adane,1 Tadele Girum,1 Wako Golicha Wako2 1Department of Public Health, Wolkite University, Wolkite, Southwest Region, Ethiopia; 2School of Public Health, Bule Hora University, Bule Hora, South Region, EthiopiaCorrespondence: Abebaw Wasie Kasahun Email abebawasie@gmail.comBackground: Ethiopia has made great strides on under-five and maternal mortality reduction as demonstrated by achieving the millennium development target of child mortality reduction by the start of 2015. According to a recent demographic and health survey report, Ethiopia has a 67 per 1000 under-five mortality rate and a 412 per 100,000 live births maternal mortality ratio. The current trend of maternal and child mortality reduction is not enough to meet sustainable development goal three (SDG3) of maternal and child mortality reduction target which is set to reduce the maternal mortality ratio to below 70/100,000 live births in all countries. This paper aimed to model the effect of scaling up family planning on pregnancies, live births, stillbirths, abortions and maternal mortality in Ethiopia.Methods: We used the Spectrum software package to model the impact of family planning on maternal survival and other maternal health metrics. Spectrum has different modules consisting of demproj module (demographic projection), famplan module (family planning), LiST (life saved tool), and AIM (aids impact model). We used Demproj, Famplan and LiST modules for this particular paper. Baseline national data were taken from findings of the Ethiopian demographic and health survey 2016, and World Bank and World Health Organization country specific reports.Results: Total fertility rate will decline to 2.3 children per women by the year 2030 when contraceptive prevalence is scaled up by 2% annually from 2016 to 2030. As a result of continuous scaling up of contraceptive use, around 3.17 million unintended pregnancies can be averted. Unmet need for family planning will significantly decline to 11.7% by 2030. Ninety-four thousand unsafe abortions could be averted and 1233 additional maternal lives could be saved by the end of 2030 in Ethiopia.Conclusion: Scaling up family planning has shown a significant effect to meet the SDG3 maternal mortality reduction target. A considerable proportion of unintended pregnancies and unsafe abortions can be averted by scaling up contraceptive prevalence by 2% annually until 2030. Family planning is effective and a less costly intervention to reduce maternal mortality in countries with high fertility; hence, it is highly recommended to rampup all efforts to scale up contraceptive use for improving maternal health status in Ethiopia.Keywords: family planning, maternal survival, spectrum modeling, Ethiopia